Strengthening the railway track on sections with heavy and high-speed train traffic - Auyesbayev, Е. Т.; Arpabekov, М. И. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
This study describes the ways and methods of strengthening the lower and upper structure of the railway track for separate sections with heavy and high-speed train traffic. The dimensions of the rail settlements in the center of the car wheel, methods of reducing the elastic vertical deformations of the upper structure of the railway track under the trains are proposed, the proposed track designs for the heavy traffic of freight trains are given. Increasing the strength of soft soils at the top of the subgrade to the level of strong and hydrophobic ones in a short time, possibly by including soil stabilization of the main site in the program of major or medium repairs of the track. This requires the use of high-performance technologies and mechanization - for example, cold recycling technology. The necessary machines and mechanisms for stabilizing the soil of the main site of the railway subgrade used in transport construction are cement trucks, distributors of cement (or ash-cement mixture), road milling machines and recyclers, motor graders, watering machines, rollers, etc. In addition, the technical requirements for high-speed passenger trains are considered.